1996
DOI: 10.1002/mrm.1910360521
|View full text |Cite
|
Sign up to set email alerts
|

Temporally resolved 3D phase‐contrast imaging

Abstract: A conventional 3D phase contrast acquisition generates images with good spatial resolution, but often gives rise to artifacts due to pulsatile flow. 2D cine phase contrast, on the other hand, can register dynamic flow, but has a poor spatial resolution perpendicular to the imaging plane. A combination of both high spatial and temporal resolution may be advantageous in some cases, both in quantitative flow measurements and in MR angiography. The described 3D cine phase contrast pulse sequence creates a temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
158
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 11 publications
0
158
0
Order By: Relevance
“…6a. In this case, previously reported methods relying on in-plane velocity measurements and evaluation of PWV along a vessel centerline (29)(30)(31)(32)(33)(34) are no longer applicable. Note also that the complex aortic shape and in particular the sharp bending of the distal descending aorta in this patient (see Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6a. In this case, previously reported methods relying on in-plane velocity measurements and evaluation of PWV along a vessel centerline (29)(30)(31)(32)(33)(34) are no longer applicable. Note also that the complex aortic shape and in particular the sharp bending of the distal descending aorta in this patient (see Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, more comprehensive three-dimensional (3D) CINE techniques in combination with three-directionally encoded velocities (flow-sensitive four-dimensional [4D] MRI) have been reported that provide information on multidirectional in vivo blood flow with full volumetric coverage of the vessel of interest (29)(30)(31)(32)(33)(34). It was the purpose of this study to investigate if PWV can be reliably estimated from 3D CINE PC data despite its lower temporal resolution by exploiting its full volumetric coverage.…”
mentioning
confidence: 99%
“…Hence, in several 2D throughplane PC studies of maximum velocity and flow determinations in stenotic vessels, a multi-slice procedure was used [11,20]. With the advent of three-dimensional, three-directional velocity encoding sequences (here denoted 4D PC) [21][22][23], the possibility has emerged to quantify velocity and flow in multiple 4 dimensions, and in addition to visualize blood flow by streamlines and pathlines. These powerful possibilities offered by 4D PC have found a number of applications, and 4D PC has started to go beyond a visualization tool into a quantitative technique for extraction of velocity, flow and hemodynamically derived parameters such as wall shear stress [24] and kinetic energy [25].…”
Section: An Alternative Non-invasive Methods For Blood Velocity Measurmentioning
confidence: 99%
“…Recently, improved time-resolved (CINE) 3D PC MRI techniques using electrocardiography (ECG) gating and advanced navigator respiration control (flow-sensitive four-dimensional [4D] MRI) have been successfully applied for the analysis of pulsatile 3D blood flow in the aorta (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Such techniques offer the opportunity for the detailed analysis of pulsatile 3D blood flow but require scan times up to 20 min.…”
Section: Contrast-enhanced (Ce) Mr Angiography (Mra) Is An Establishementioning
confidence: 99%